El debate de género y la interculturalidad en la literatura infantil. Un análisis bibliográfico de 2013 a 2021 - Rodriguez Castillo, Laury Vanessa (Universidad Antonio Nariño, 2022)
This compilation monograph analyzes articles published in the last 18 years, which present reflections on children's literature with "complex" themes such as gender, afro and violence. The purpose of the analysis is to identify some research contributions that allow us to have a general understanding of how these "complex topics" are being addressed in the literary text, the role of the adult and to inquire about the ideological and cultural perspectives in these reflections. Finally, we reflect on the contributions of gender and intercultural perspectives in children's literature, as well as some relationships that arise with the educational context.